Neu=Angeordnete Lotterey In Dantzig. Anno 1698. - Stolle, Jan Zachariasz (16..-1720) (Druckts ... Johann=Zacharias Stolle, 1699)
Rozporządzenie Rady Miasta Gdańska dotyczące zorganizowanej w Gdańsku loterii w roku 1698.